Uma estratégia para a aplicação de robotic process automation nos processos de gestão de recursos humanos - Esteves, David João Pedreiro (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management